Analysis and Design of Ticketing Application System (Case Study: Bebek Kaleyo) - Heri Ngarianto; Ahmad Fikri Mulaputra; Fanny Septiany; Tiara Delima (Bina Nusantara University, 2023)
Bebek Kaleyo is a restaurant chain with several outlets in the food business. Information technology (IT) equipment is used extensively in Bebek Kaleyo's operating processes, and any problems with the IT hardware are escalated to the IT department for solutions. However, each restaurant branch's reporting of interruptions is still done by hand. Based on these issues and the analysis, it is necessary to speed up the complaint procedure to guarantee quick repairs of IT equipment and successful execution of tasks. The research was conducted by examining the company's daily activities, and the results were used to develop a ticketing system for monitoring process improvements and reporting interruptions. A ticketing system that facilitates effective reporting of IT issues and monitors process improvements was designed and developed as part of this research using the prototype methodology. The installed ticketing system helps users at each branch report problems, keep track of repairs, and improves the efficiency and quality of service provided by the IT department in support of the supply and use of system and technology-related facilities. By using this ticketing system, Bebek Kaleyo hopes to improve overall process efficiency while streamlining the process of reporting IT concerns. This solution gives branch users the ability to discuss IT issues with the IT department in an efficient manner, which improves the organization's operational performance.